Culture-Laden Extensive Reading Through Team-Based Mobile Learning: Effects on Intercultural Communicative Competence And Reading Motivation - David Imamyartha; Eka Wahjuningsih; Areta Puspa; Rizki Febri Andika Hudori; Mutiara Bilqis (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2022)
With the advent of technology, cultural diversities encouraged language teachers in higher education to push the current pedagogical boundaries to seek the best fits for cultural learning. This study engaged with the pursuit of such pedagogies by experimenting with the integration of team-based mobile learning (TBML) in extensive reading classes mediated by a mobile instant messaging, Telegram. The research findings have statistically acknowledged that TBML can develop EFL readers’ intercultural knowledge and understanding. The technological and socio-constructivist affordances of TBML also elevate reading motivation as the springboard for developing Intercultural communicative competence (ICC). Research implications and limitations are also discussed.